Correlation of hearing aid use and quality of life in elderlies: A systematic review - Saraswati, Innes Andini; Utomo, Bambang Suprayogi Resi; Trixie, Joue Abraham (Oto Rhino Laryngologica Indonesiana, 2024)
Background: Aging can lead to degeneration processes in multiple organs, including the auditory organs, resulting in hearing loss. Hearing loss in the elderly often affects their quality of life (QOL). One of the procedures to improve this could be done by fitting hearing aids (HA). According to the National Center of Health Statistics (NCHS) data, hearing loss in people over 65 years old is 26.8%. However, only 14.4% use hearing aids. Purpose: To find out the correlation between the use of hearing aids and the quality of life of the elderly. Literature review: This was a systematic review with an observational study approach. Data analysis was performed using Review Manager software. QOL was assessed with the Hearing Handicap Inventory for Elderly (HHIE) questionnaire. Afterwards, comparing between the elderly who used HA and those who did not use HA. Results: The literature identified from the medical database reached 728 features, but only 4 met the criteria. From the research results, it was found that there was a statistically significant difference in HHIE scores between elderly people who used and did not use hearing aids. In social HHIE p=0.03 (p<0.05), emotional HHIE p=0.02 (p<0.05), and total HHIE p=0.006 (p<0.05). Total HHIE, a combination of social and emotional HHIE, described the overall quality of life. Conclusion: Hearing aids were considered effective for reducing limitations due to hearing loss, especially communication in the elderly. In other words, the quality of life in the elderly who used HA was better than in the elderly who did not use HA. Keywords: elderly, hearing loss, hearing aids, quality of life   ABSTRAK Latar belakang: Penuaan dapat menyebabkan proses degenerasi pada berbagai organ, termasuk organ auditori sehingga terjadi gangguan pendengaran. Gangguan pendengaran pada lansia seringkali memengaruhi kualitas hidupnya. Salah satu upaya untuk memperbaiki hal tersebut dapat dilakukan dengan pemasangan alat bantu dengar (ABD). Menurut data National Center of Health Statistics (NCHS), gangguan pendengaran di usia lebih dari 65 tahun mencapai 26,8%; tetapi, hanya 14,4% diantaranya yang menggunakan alat bantu dengar. Tujuan: Mengetahui hubungan penggunaan alat bantu dengar terhadap kualitas hidup lansia. Tinjauan Pustaka: Menggunakan metode systematic review dengan pendekatan studi observasional. Analisis data dilakukan dengan perangkat lunak Review Manager. Kualitas hidup dinilai dengan kuisioner Hearing Handicap Inventory for Elderly (HHIE), lalu dibandingkan antara lansia yang menggunakan dan tidak menggunakan ABD. Hasil: Literatur yang teridentifikasi dari medical database mencapai 728 tulisan, tetapi hanya 4 yang memenuhi kriteria. Dari hasil penelitian didapatkan bahwa terdapat perbedaan skor HHIE yang signifikan secara statistik antara lansia yang menggunakan dan tidak menggunakan alat bantu dengar. Pada HHIE sosial didapatkan p=0.03 (p<0.05), HHIE emosional p=0.02 (p<0.05), dan HHIE total p=0,006 (p<0,05). Kualitas hidup secara keseluruhan digambarkan oleh HHIE total yang merupakan gabungan antara HHIE sosial dan emosional. Kesimpulan: Alat bantu dengar dinilai efektif untuk menurunkan keterbatasan akibat gangguan pendengaran, terutama komunikasi pada lansia. Dengan demikian kualitas hidup pada lansia yang menggunakan ABD lebih baik daripada lansia yang tidak menggunakan ABD. Kata kunci: lansia, gangguan pendengaran, alat bantu dengar, kualitas hidup